Navigating the transition: Implementing competency-based medical education in medical curriculum in India - Aditi Aikat (Asian Journal of Medical Sciences, 2024)
The road to implementation of competency-based medical education (CBME) in the medical curriculum in India has both challenges and windows of opportunities in its folds. The hindrances identified were reluctance to change, capacity building of faculties, lack of infrastructural support, and methods of assessment. Notwithstanding, CBME has the potential to ensure that the Indian medical graduates are equipped with better clinical skills, and learner-centric education, that aligns well with individual competence, and community healthcare needs. Effective navigation through this transition calls for collaborative efforts among academicians, regulatory bodies, and related stakeholders while drawing from relevant successful models of our country itself. It is imperative to address the challenges concerning capacity building of faculties, resource allocation, and assessment methodology for successful implementation. Given appropriate adoption, the CBME-based curriculum can go a long way to deliver quality healthcare.